Beyond deficit discourse: reframing debate in Indigenous education - Kerry McCallum; LJ Waller; Tanja Dreher (2019)
In this essay we explore how digitization is affecting Indigenous peoples’ participation in debates around education. While there has been extensive research about the impacts of technology in Indigenous education, there has been little research examining the impacts of digital media on public debate about Indigenous education. This paper documents how First Nations communities are using their own media to reject the mainstream media’s truancy discourse and develop deeper, broader, more positive conversations on school attendance.